Achieving high quality standards in laparoscopic colon resection for cancer: A Delphi consensus-based position paper. Issue 4 (April 2018) - Lorenzon, Laura; Biondi, Alberto; Carus, Thomas; Dziki, Adam; Espin, Eloy; Figueiredo, Nuno; Ruiz, Marcos Gomez; Mersich, Tamas; Montroni, Isacco; Tanis, Pieter J.; Benz, Stefan Rolf; Bianchi, Paolo Pietro; et al.
Abstract: Aim: To investigate the rate of laparoscopic colectomies for colon cancer using registries and population-based studies. To provide a position paper on mini-invasive (MIS) colon cancer surgery based on the opinion of experts leader in this field. Methods: A systematic review of the literature was conducted using PRISMA guidelines for the rate of laparoscopy in colon cancer. Moreover, Delphi methodology was used to reach consensus among 35 international experts in four study rounds. Consensus was defined as an agreement ≥75.0%. Domains of interest included nosology, essential technical/oncological requirements, outcomes and MIS training. Results: Forty-four studies from 42 articles were reviewed. Although it is still sub-optimal, the rate of MIS for colon cancer increased over the years and it is currently >50% in Korea, Netherlands, UK and Australia. The remaining European countries are un-investigated and presented lower rates with highest variations, ranging 7–35%. Using Delphi methodology, a laparoscopic colectomy was defined as a "colon resection performed using key-hole surgery independently from the type of anastomosis". The panel defined also the oncological requirements recognized essential for the procedure and agreed that when performed by experienced surgeons, it should be marked as best practice in guidelines, given the principles of oncologic surgery be respected (R0 procedure, vessel ligation and mesocolon integrity). Conclusion: The rate of MIS colectomies for cancer in Europe should be further investigated. A panel of leaders in this field defined laparoscopic colectomy as a best practice procedure when performed by an experienced surgeon respecting the standards of surgical oncology.